Iraqi EFL University Students and the Communicative Approach - Khaleel, Asst. Lect. Entidhar; Jebur, Asst. Lect. Abid Ali Muhannah (Manar Elsharq Journal for Literature and Language Studies, 2026)
The communicative approach, also known as Communicative Language Teaching (CLT), has become one of the most influential approaches in English language teaching worldwide. In Iraq, English as a Foreign Language (EFL) university students often face difficulties in developing communicative competence despite years of studying English. Traditional teaching methods focusing on grammar translation and memorization continue to dominate many Iraqi classrooms, limiting students’ opportunities for authentic communication. This research examines the communicative approach and its impact on Iraqi EFL university students. It discusses the historical development of CLT, its principles, characteristics, classroom activities, advantages, challenges, and its implementation in Iraqi universities. Furthermore, the study highlights communicative competence, student motivation, classroom interaction, and the role of teachers within communicative classrooms. The paper also reviews recent Iraqi and international studies related to communicative language teaching and Iraqi EFL learners. The findings indicate that the communicative approach positively affects students’ speaking abilities, interaction, confidence, motivation, and language proficiency. However, several obstacles hinder effective implementation, including overcrowded classrooms, limited teacher training, lack of resources, examination systems, and students’ anxiety. The study concludes with pedagogical recommendations for improving communicative teaching practices in Iraqi universities.